In vivo degradation of rat C1q induced by intravenous injection of soluble IgG aggregates. - Veerhuis, R (1985)
Immune complexes are able to bind and activate the first component of complement, C1. Upon activation of C1, C1r and C1s are rapidly inactivated by C1-In which also forms a complex with these two subcomponents, resulting in their release from C1-immune aggregate complexes. The fate of C1q after the binding C1 to immune complexes in vivo is not clear and, therefore the clearance of radiolabelled rat C1q was investigated in normal rats and in rats receiving soluble aggregated human IgG. 125I-labelled rat C1q was cleared with a half-life (T 1/2) of 12.4 hr in normal rats. Injection of AIgG into rats that had previously received 125I-C1q accelerated the clearance of 125I-C1q, resulting, finally, in a T 1/2 of 53 min. The levels of circulating endogenous C1q were also followed using haemolytic titrations and immunochemical measurements. Directly after injection of AIgG into rats, there was a rapid decrease in C1q haemolytic activity to less than 25% of the initial value after 10 min. The rate of disappearance of C1q antigen, was, however, much slower, the lowest concentration being 30% at 2 hr. C1q haemolytic activity and the C1q antigen level returned to virtually normal values after 24 hr. Plasma samples were taken at different time intervals after the injection of AIgG and subjected to gel filtration on Sephacryl S-400 columns. It was found that, in the 10 min samples, C1q antigen and C1q haemolytic activity, each with an estimated molecular weight (MW) of 400,000, were detected together. In addition, there was C1q antigen with a MW of less than 69,000 without C1q haemolytic activity. SDS-PAGE analysis of the various serum samples indicated that the low MW C1q antigen had an apparent MW of 25,000. Measurement of uptake of 125I-C1q in various organs indicated that the main site of clearance of 125I-C1q is the liver.